Pengaruh Promosi Jabatan, Kenaikan Gaji, Leadership Terhadap Meningkatnya Kualitas Sumber Daya Manusia The Effect of Position Promotion, Salary Increase, Leadership on Improving the Quality of Human Resources - Suginam Suginam; Joli Afriany; Wily Julitawaty; Nurlaila Nurlaila (Universitas Medan Area, 2022)
Human resources determine the progress and development of a company and is the most important aspect to pay attention to, if it is not noticed what happens is the number of negative impacts that will be received by the company such as operational delays, unsatisfactory performance, giving a bad image of resource management humans and many other risks. In improving the quality of human resources, it can be done by emotional provoking human resources themselves, many studies have discussed the importance of maintaining and considering improving the quality of human resources, one of which is done by knowing things related to improving the quality of human resources. . This study will look at the effect of job promotions, salary increases, leadership on the quality of human resources with the results obtained that the independent variables of salary increases and promotions have a significant value that has a positive effect on improving the quality of human resources, while leadership results in rejection of the level of influence on improving the quality of human resources with a negative significance value.